THE IMPACT OF FOREIGN DIRECT INVESTMENT ON ECONOMIC GROWTH IN INDONESIA, 1980-2004: A CAUSALITY APPROACH - Wahyudi, Setyo Tri (Journal of Indonesian Economy and Business, 2009)
Foreign investment, in addition to domestic investment, is one of the driving sources of a nations economy, because of its ability to create jobs and allow the transfer oftechnology that in turn encourages economic growth. Significant role contributed by these investments, in the context of Indonesia, can be seen from its contribution to the national economy.This study aims to determine the relationship between investment and economic growth in Indonesia. Using the data of Foreign Direct Investment (FDI) and GDP on 1980-2004 periods, and method of causality, this study tried to answer the question of whether investment causes economic growth or whether economic growth causes investment.To examine the relationship between two variables, there are three steps test conducted, unit roots test (using the ADF test); co integration test (using the Johansen cointegration test); and causality test (using the Granger Causality test). Conclusion indicated that investment affects economic growth.Keywords: Foreign direct investment, economic growth, granger causality.